Penyerapan I-131 yang Tidak Disengaja pada Karsinoma Ovarium pada Seorang Pasien dengan Karsinoma Tiroid yang Terdiferensiasi: Laporan Kasus: Laporan Kasus - Sihombing, Amordekhai Imvan Parlindungan; Nugrahadi, Trias; Kartamihardja, Achmad Hussein Sundawa (PT Kalbe Farma Tbk., 2026)
Introduction: Radioactive iodine (I-131) therapy is an essential component in the management of differentiated thyroid carcinoma (DTC) following total thyroidectomy. Post-therapy whole-body scintigraphy (PT-WBS) with I-131 aims to detect residual thyroid tissue, recurrence, or metastatic spread. Radioiodine uptake outside the thyroid region may suggest metastases or false-positive findings, thus requiring careful interpretation. Case: A 47-year-old woman with differentiated thyroid carcinoma (DTC) underwent I-131 therapy. The PT-WBS and single photon emission computed tomography/computed tomography (SPECT/CT) revealed no I-131 uptake in the thyroid bed, but instead showed unexpected I-131 uptake in bilateral ovarian masses. Subsequent histopathological and immunohistochemical evaluation after total hysterectomy with bilateral salpingo-oophorectomy confirmed that the masses were ovarian carcinoma. Discussion: Radioiodine uptake in ovarian carcinoma is extremely rare and may be attributed to the expression of the sodium-iodide symporter (NIS) in the ovarian surface epithelium (OSE). Other contributing factors may include increased tumor vascularity, local inflammation, and enhanced capillary permeability that facilitate iodine retention. Conclusion: This case highlights the importance of considering non-thyroidal malignancies in the interpretation of PT-WBS findings, particularly when atypical uptake is observed.